The impact of digital technology use on EFL students’ English academic performance: The mediating roles of emotional intelligence and learning engagement - Yanhong Shao; Jingtao Wu; Yan Li; Quan Lu; Zunyang Wang (BMC Psychology)
Abstract Background For English as a Foreign Language (EFL) learners, English academic performance serves as a key determinant of their educational attainment and psychological well-being. While previous studies have pinpointed digital technology use, emotional intelligence, and learning engagement as key determinants of English academic performance, the specific mechanisms through which digital technology use impacts EFL students’ English academic performance via emotional intelligence and learning engagement remain underexplored. Methods This study employed random sampling to investigate how digital technology use affects the academic performance of EFL students, with a particular focus on the mediating roles of emotional intelligence and learning engagement. We administered a survey to 931 EFL students (Mean = 17.52, SD = 0.531) in Yancheng City, Jiangsu Province, utilizing questionnaires that assessed digital technology use, emotional intelligence, and learning engagement. The relationships between these variables and academic performance were examined using structural equation modeling. Results The study revealed that: (1) Digital technology use has a positive and direct effect on the English academic performance of EFL students (p < 0.01); (2) Emotional intelligence mediates the relationship between digital technology use and English academic performance, with an indirect effect of 0.252 (95% CI [0.048, 0.600]); (3) Learning engagement mediates the relationship between digital technology use and English academic performance, with an indirect effect of 0.712 (95% CI [0.215, 1.252]); (4) Emotional intelligence and learning engagement jointly play a serial role in the relationship between digital technology use and English academic performance, with an indirect effect of 0.075 ( 95% CI [0.011, 0.231]). Conclusion The findings provide empirical support for a more nuanced understanding of how digital technology can enhance the English academic performance of EFL students by shaping their emotional intelligence and learning engagement. Moreover, the findings suggest EFL educators can enhance students’ English academic performance by strategically incorporating emotion-regulation training through mindfulness exercises while implementing interactive digital tasks like collaborative projects, thereby leveraging the dual mediating effects of emotional intelligence and learning engagement in technology-enhanced learning environments.